Simulation and Analysis of Oil Churning Power Loss in Electric Drive Planetary Gears Based on the CFD Method - Tang Pei; Wang Le; Ren Shaoying; Li Shanshan (Jixie chuandong)
The research on electric drive wheel technology is an important direction of the research on the new energy drive system in the future. With the increasing requirements of the electric drive wheel on the speed, the oil churning power loss has become a non-negligible part, even up to 50%-80% of the total power loss. The existing calculation method of churning loss mainly adopts simple empirical formula, which cannot be applied to complex planetary gear transmission. The splash lubrication of the two-stage planetary gear drive is simulated by computational fluid dynamics (CFD) software and C language user defined function (UDF), and the visualization of oil gas two-phase transient flow field is realized; by extracting the surface pressure and the viscous force, the churning loss of the sun gears, planet gears and planet carriers are obtained; the simulation and analysis of the 25 working conditions show that the churning loss varies with the immersion depth and speed; the results show that the oil churning power loss increases with the oil immersion depth and the speed, and there is no obvious inflection point. To achieve the minimum oil stirring loss, the minimum oil immersion depth should be taken on the premise of ensuring full lubrication.